VIOLENCE IN EDUCATION: IMPACT ON FORMATION OF FUTURE LEBANESE LEADERS - Kayrouz, Akl; Atala, Issam (European Scientific Journal, ESJ, 2015)
History of empires and nations in a particular civilization is remembered by the scientific and academic discoveries. Greeks, Roman, Persian or other empires are mostly their military conquests and glories which faded away with time, while the taught ideologies, thoughts and inventions remain basic pillars in the development of human history, civilization and scientific discoveries. In the modern world man undertook many leaps into uncovering what previously were viewed as national mysteries and secrets. Science and technology have transported man to outer space, reaching other planets, travelling deeply in the fields of medicine, communication, transportation, electronics and continual creativity; yet that same man, remains enslaved to its own weaknesses and shortfalls. The scientific superhuman, in spite of the discoveries, focused also on self- destruction. Weapons of mass destruction are endlessly invented, poverty and misery offers over forty percent of the world population (2.6 billion humans), while over one thousand billions U.S. dollars are spent yearly on wars, destruction of humans and the environment. The authors chose to focus on (a) providing general but clear definition of educational objectives in Lebanon; (b) identifying the Lebanese educational socio-political system; (c) highlighting some deficiencies of the curricula offered at educational institutions, beginning with the first grades till the graduate studies at universities; (d) examining the family influence; (e) stressing the socio-religious, political ideological indoctrination. The study also highlights the negative effects caused by unqualified, untrained and unethical teaching staff in most institutions which resemble business bazaars where profit and money are the driving engines.